Determining technological parameters for the additive electron-beam surfacing of blanks for medical implants made of Zr-Ti-Nb alloy - Matviichuk, Vladyslav; Nesterenkov, Vladimir; Efanov, Volodymyr; Zavgorodny, Olexandr; Bilyi, Roman (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the alloys of the Zr-Ti-Nb system, which better than titanium alloys meet the criterion for mechano-biocompatibility of the material for dental implants. The choice of this material is due to the fact that zirconium alloys are free of toxic elements and have a low modulus of elasticity. Under modern conditions of active implementation of additive technologies for the manufacture of metal products, the use of zirconium alloys for 3D printing is a promising area. Such technologies include electron-beam growing of products. The task solved in this work relates to the lack of technological modes for electron beam technology, specifically for zirconium alloy. A rational regime has been determined, under which samples were grown from the alloy of the Zr-Ti-Nb system with a smooth surface, uniform structure, and no internal defects. It should be especially noted that the modulus of elasticity of the material of the manufactured samples was 59.8 GPa, which is two times lower than that of the titanium alloy Ti-6Al-4VELI (113.8 GPa) and is closer to the modulus of elasticity of human bone (30 GPa). The results are explained from the point of view of physical-mechanical processes occurring in the metal during layer-by-layer surfacing under different conditions. These conditions were created by different values of technological parameters. Special feature of the results is that the formed requirements for the structure and properties of zirconium blanks were based on known dependences for titanium alloys. The findings showed that electron beam growing could become an alternative technology for manufacturing implant blanks from low-modulus zirconium alloy. The scope and conditions of practical use of the results extend to materials for implants in dentistry and, in the future, in orthopedics